Propostas para aceleração de duas metas em atraso da agenda 2012: programa de metas do município de São Paulo - Freitas, João Paulo N. Sabino de (2011)
The objective of this paper is to suggest alternatives for the acceleration of two goals within the São Paulo City Goals Program („2012 Agenda‟): goal number 78 (implementation of 2 training centers for recycling cooperative members) and goal number 80 (creation of 1,000 Voluntary Collection Points for recycled material). At the beginning of this paper the reported level of completion was 0%. The diagnosis detected flaws in the execution process as well as in the design and monitoring phases. A set of recommendations were then designed in order to achieve the selected goals. The paper highlights necessary actions, managers, deadlines, budget impacts and risks. These recommendations include improvements in the monitoring system (with more frequent updates), the use of timelines to assist the execution process and the creation of new structural alternatives for implementing the delayed goals. Additionally, the diagnosis allowed the conclusion that there is an absence of incentive mechanisms for public managers in the delivery of the Program‟s goals. In light of these conclusions, general recommendations were then proposed for the design of the new and subsequent Goals Program, inspired on performance based management experiences.